Assessing the effects of hybridization and precipitation on invasive weed demography using strength of selection on vital rates. Issue 1 (December 2016) - Teitel, Zachary; Klimowski, Agnieszka; Campbell, Lesley
Abstract Background As global climate change transforms average temperature and rainfall, species distributions may meet, increasing the potential for hybridization and altering individual fitness and population growth. Altered rainfall specifically may shift the strength and direction of selection, also manipulating population trajectories. Here, we investigated the role of interspecific hybridization and selection imposed by rainfall on the evolution of weedy life-history in non-hybrid (Raphanus raphanistrum ) and hybrid (R. raphanistrum x R. sativus ) populations using a life table response experiment. Results In documenting long-term population dynamics, we determined intrinsic (r ) and asymptotic (λ ) population growth rates and sensitivities, a measure of selection imposed on demographic rates. Hybrid populations experienced 8.7-10.3 times stronger selection than wild populations for increased seedling survival. Whereas crop populations generally exhibit little dormancy and wild populations often exhibit dormancy, non-hybrid populations experienced 10% stronger selection than hybrid populations for exhibiting seed dormancy. Selection on survival-to-flowering in wild, not hybrid, populations declined marginally with increasing soil moisture. Hybrid populations exhibited greaterr, but notλ, than wild populations regardless of moisture environment. In general, fecundity contributed most to differences in λ but fecundity only contributed positively to hybrid λ relative to wild λ when precipitation was altered (either higher or lower than control) and not under control watering conditions. Conclusions Selection on key demographic traits may not change dramatically in response to rainfall, and hybridization may more strongly influence the demography of these weedy species than rainfall. If hybrid populations can respond to selection for increased dormancy, this may make it more difficult to deplete weed seed banks and increase the persistence of crop genes in weed populations.